Natural History of Untreated Prostate Specific Antigen Radiorecurrent Prostate Cancer in Men with Favorable Prognostic Indicators - Neil E. Martin; Ming-Hui Chen; Clair J. Beard; Paul L. Nguyen; Marian J. Loffredo; Andrew A. Renshaw; Philip W. Kantoff; Anthony V. D’Amico (Prostate Cancer)
Background and Purpose. Life expectancy data could identify men with favorable post-radiation prostate-specific antigen (PSA) failure kinetics unlikely to require androgen deprivation therapy (ADT). Materials and Methods. Of 206 men with unfavorable-risk prostate cancer in a randomized trial of radiation versus radiation and ADT, 53 experienced a PSA failure and were followed without salvage ADT. Comorbidity, age and established prognostic factors were assessed for relationship to death using Cox regression analyses. Results. The median age at failure, interval to PSA failure, and PSA doubling time were 76.6 years (interquartile range [IQR]: 71.8–79.3), 49.1 months (IQR: 37.7–87.4), and 25 months (IQR: 13.1–42.8), respectively. After a median follow up of 4.0 years following PSA failure, 45% of men had died, none from prostate cancer and no one had developed metastases. Both increasing age at PSA failure (HR: 1.14; 95% CI: 1.03–1.25; P=0.008) and the presence of moderate to severe comorbidity (HR: 12.5; 95% CI: 3.81–41.0; P<0.001) were significantly associated with an increased risk of death. Conclusions. Men over the age of 76 with significant comorbidity and a PSA doubling time >2 years following post-radiation PSA failure appear to be good candidates for observation without ADT intervention.